Ancient Tragedy and the Interpretation of the Historical Present: Experience of the King Artavazd II - Stepanyan, Albert (History and Culture, 2025)
The paper is intended to study the “Life of Crassus” by Plutarch, particularly, those fragments that concern the history of Greater Armenia under Artavazd II (55-34 BC.). International relations of the age have been discussed in light of Hellenistic and Roman juridical concepts of “friend” and “ally”.  The fact is especially underlined that Tigran II was in a friendly relationship simultaneously with Rome and Parthia in the last period of his reign. First of all, it demanded of him not to support one super-state against the other. However, Romans frequently “confused” this kind of relationship and identified it with that which was demanded by allies who were obliged to support them with material means and military forces. This kind of confusion is traceable during the Parthian company of Crassus (54-53 BC.). The triumvir tried to force Artavazd II to pay the obligations of an ally. The King declined the proposal and kept the side of the Parthian king Orodes II. At the same time, he refused to undertake any action against the Romans. Both kings agreed that Crassus acted with egoistic goals and did not express the will of the Roman People (Populus Romanus). This idea was laid under the “Artaxata performance” where Crassus was identified with the hero Euripides’ “Bacchae” – Prince Pentheus whose frantic actions caused his death at the hands of Dionysus. This must be estimated as a message to Rome to restore friendly and just relations.
Keywords: Aristotle; Euripides; King Artavazd II; The Theory of Ancient Theatre; The relationship Between Tragedy and Historiography; Crassuss’ Eastern Company